2014
DOI: 10.1016/j.avb.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Sexual abuse of children and youth in residential care: An international review

Abstract: Sexual abuse of children and youth in residential care. An international review Early Child Development and Care 133: 101-114.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…It was also highly concerning that a small proportion of these young people were sexually aggressive towards female staff members, and in rare cases towards men who they considered to be 'weak'. This might reflect the strength of the young person's sexual deviance, a sign of their own trauma, or an act of resistance to adult authority (Timmerman & Schreuder, 2014). Wylie & Griffin (2013) note that it is crucial that while services work holistically with these young people, they do not forget that some of these young people do pose serious risks -and that forgetting about this risk would be both unsafe and unethical.…”
Section: Discussionmentioning
confidence: 99%
“…It was also highly concerning that a small proportion of these young people were sexually aggressive towards female staff members, and in rare cases towards men who they considered to be 'weak'. This might reflect the strength of the young person's sexual deviance, a sign of their own trauma, or an act of resistance to adult authority (Timmerman & Schreuder, 2014). Wylie & Griffin (2013) note that it is crucial that while services work holistically with these young people, they do not forget that some of these young people do pose serious risks -and that forgetting about this risk would be both unsafe and unethical.…”
Section: Discussionmentioning
confidence: 99%
“…This confusion is evident in a number of previous studies: where young people, staff in residential care and the broader community have found it difficult to differentiate different types of behaviours and may reinforce skewed beliefs (Green & Masson, 2002;Timmerman & Schreuder, 2014). In some instances, adults have determined that due to their developmental stage, young people were likely to engage in sexual relationships and that this was a normal and natural part of growing up.…”
Section: Differentiating Sexually Abusive Behaviours From Developmentmentioning
confidence: 99%
“…Although much of this evidence is historical and relates to residential facilities that were run quite differently to the ways that residential care is provided in contemporary times, child sexual abuse remains a risk for many young people in care. In addition to child sexual abuse perpetrated by adults within residential care settings, greater attention has recently focused on problematic sexual behaviour amongst young people, and the exploitation of young people by adults outside the residential care setting (Hallett, 2015;Timmerman & Schreuder, 2014).…”
Section: Executive Summarymentioning
confidence: 99%
See 2 more Smart Citations